Pregnancy Outcomes Reported During the 13-Year TREAT Registry: A Descriptive Report. (November 2018) - Lichtenstein, Gary; Feagan, Brian; Mahadevan, Uma; Salzberg, Bruce; Langholff, Wayne; Morgan, G.; Safdi, Michael; Nissinen, Riikka; Taillard, François; Sandborn, William; Cohen, Russell
Abstract OBJECTIVES We described pregnancy outcomes in Crohn's disease (CD) patients enrolled in the TREAT Registry who received infliximab before, or during pregnancy and those not treated with infliximab or any biologic agent. Methods In the TREAT Registry (1999–2012), pregnancy outcomes were analyzed from maternal and paternal patients exposed to infliximab ≤365 days (gestational exposure), >365 days (pre-gestational exposure) of pregnancy outcome or without infliximab exposure (non-biologic exposed). "Healthy infants" were defined as those with no congenital abnormalities, neonatal complications (e.g., jaundice, prematurity, heart murmur, cortical vision/fine motor delay, cardiac failure, hemophilia, or torticollis), prolonged hospitalization, or those who received no special treatment. Disease activity and concomitant medications were also evaluated. Results Overall, 92.3% (324/351) of pregnancies had known outcomes. The majority of both maternal pregnancies (92.6, 91.2, and 87.8%) and partner outcomes (92.7, 93.8, and 91.7%) resulted in live births of healthy infants across gestational, pre-gestational, and non-biologic exposure groups, respectively. Among these, rates of neonatal complications were low for both maternal (6.2, 7.0, and 8.5%), and partner outcomes (4.9, 0, and 0%) in gestational, pre-gestational, and non-biologic exposure groups, respectively. Among maternal pregnancies, numerically higher rates of spontaneous abortions were observed for the gestational exposure group than for the pre-gestational or non-biologic exposed groups. Conclusions The clinical condition of infants born to women with gestational infliximab exposure was similar to those without exposure. Although a lower live birth rate was reported among infliximab-exposed women, these patients had more severe CD and were more likely to have been exposed to immunosuppressives.